Bilateral optic disc edema as a possible complication of cabozantinib use–a case report. Issue 3 (May 2023) - Huang, Yu-Te; Lin, Chun-Ju; Tsai, Yi-Yu; Hsia, Ning-Yi
Introduction: Cabozantinib, which was approved by the Food and Drug Administration (FDA) in 2012, is a tyrosine kinase inhibitor widely used in the treatment of metastatic renal cell carcinoma (RCC) and medullary thyroid carcinoma. To date, no ocular adverse events have been reported by the FDA or on the package label. Here, we described a patient with metastatic RCC who developed bilateral optic disc edema after a 4-month course of cabozantinib. Case description: A 55-year-old ethnic Chinese male with RCC with multiple metastases presented to our department with progressive blurred vision in both eyes for 1 month. He started taking cabozantinib 60 mg once daily 5 months prior to this presentation. Poor visual acuity and bilateral disc edema were then noted. Cabozantinib was discontinued after that, and 3-day pulse steroid therapy with methylprednisolone 1 g/day was given. The optic disc edema subsided gradually with limited improvement in visual acuity. Conclusion: Bilateral optic edema should be considered as a complication associated with cabozantinib. We propose discontinuation of the treatment in cases such as that, and pulse steroid therapy should be considered if there is no contraindication.